Workplace violence against emergency medicine registrars and consultants, and their experience of job safety and satisfaction - Midgley, Alexandra (Division of General Surgery, 2022)
Background: Studies have shown that healthcare workers in Emergency Units (EUs) are at a high risk of both physical and non-physical workplace violence. While several international studies have focused on the experience of workplace violence by Emergency Medicine (EM) specialist physicians, there is a paucity of data regarding that of EM physicians in training. Objectives: This study aimed to determine the amount of workplace violence (and the subtypes thereof) perpetrated against Western Cape EM registrars and consultants, and their perceived level of, and identified barriers to and facilitators of, job safety and satisfaction. Methods: This cross-sectional study relied upon responses to a survey, electronically disseminated over a 6-week period, in May/June 2018, amongst Western Cape public sector EM registrars and consultants. The primary outcome was the incidence of workplace violence experienced. The secondary outcomes were the sub-types of workplace violence perpetrated, as well as the perceived level of job safety and satisfaction, and identified barriers thereto and facilitators thereof. Results: In total, 66% of respondents had experienced at least one act of physical violence while working in Western Cape EUs, specifically by patients. Regarding non-physical violence, 90.6% of respondents had experienced at least one act of verbal harassment, 84.9% of verbal threat, and 45.3% of sexual harassment. The rates of both physical and non-physical workplace violence (especially sexual harassment), perpetrated by patients specifically, were found to be higher in female than in male respondents. Apart from acts of verbal harassment, which were perpetrated equally by patients and visitors, all other acts of physical and nonphysical workplace violence were perpetrated at a higher rate by patients than visitors. The rates of both physical and non-physical workplace violence, perpetrated by patients specifically, were found to be higher in EM consultants than in EM registrars. The factors most commonly indicated by respondents as contributory to workplace violence were patient and/or visitor alcohol use, drug use and psychiatric illness. Other factors commonly indicated were long waiting times and unmet expectations, and resultant patient and/or visitor frustration. Conclusion: Workplace violence against EM registrars and consultants is a significant problem in Western Cape EUs. The information gained during this study will be useful in improving safety and security policies at an EU (and hospital) level. It may even be applicable at a provincial (or national) level in changing legislation, in order to reduce, and ultimately prevent, workplace violence in the EU.